Village Head Leadership in the Implementation of the Carved Furniture Community Empowerment Program in Mulyoharjo Village in 2024 - Handini Maharani; Tijan Tijan (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
This study aims to analyse the leadership role of the Village Head in community empowerment programs in Mulyoharjo Village, Jepara Subdistrict, Jepara Regency, which is known as the centre of the carved furniture industry. The method used is a descriptive qualitative approach with data collection techniques through interviews and documentation. The results showed that the leadership of the Head of Mulyoharjo Village, which is democratic and participatory, has a significant influence in increasing the capacity and independence of the community, especially through the furniture industry empowerment program. The program includes training in carving skills, business management, digital marketing, and the use of appropriate technology. Although the implementation of the program has gone well, there are still challenges such as the low participation of the younger generation and limited facilities. Overall, the leadership of the Mulyoharjo Village Head contributes to strengthening local potential through a collaborative approach oriented towards sustainable development.